2017
DOI: 10.15252/embj.201694959
|View full text |Cite
|
Sign up to set email alerts
|

Id2 controls specification of Lgr5 + intestinal stem cell progenitors during gut development

Abstract: The adult intestinal stem cells (ISCs), their hierarchies, mechanisms of maintenance and differentiation have been extensively studied. However, when and how ISCs are established during embryogenesis remains unknown. We show here that the transcription regulator Id2 controls the specification of embryonic Lgr5 progenitors in the developing murine small intestine. Cell fate mapping analysis revealed that Lgr5 progenitors emerge at E13.5 in wild-type embryos and differ from the rest on the intestinal epithelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 39 publications
(88 reference statements)
3
60
0
Order By: Relevance
“…Collectively, these studies suggest that Wnt/β-catenin signaling is dispensable for proliferation during pseudostratified intestinal development. In this context, it is interesting to note that several separate studies have shown that the Wnt/β-catenin target gene, and well described adult intestinal stem cell marker, Lgr5 [13], is expressed during this time of low Wnt activity [109111]. Recent lineage tracing experiments in Lgr5-creER mice have shown that lineage tracing can occur as early as E12.5 [109].…”
Section: Early Intestine Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, these studies suggest that Wnt/β-catenin signaling is dispensable for proliferation during pseudostratified intestinal development. In this context, it is interesting to note that several separate studies have shown that the Wnt/β-catenin target gene, and well described adult intestinal stem cell marker, Lgr5 [13], is expressed during this time of low Wnt activity [109111]. Recent lineage tracing experiments in Lgr5-creER mice have shown that lineage tracing can occur as early as E12.5 [109].…”
Section: Early Intestine Developmentmentioning
confidence: 99%
“…Recent lineage tracing experiments in Lgr5-creER mice have shown that lineage tracing can occur as early as E12.5 [109]. Mechanistically, it appears that the transcription factor Id2, restricts Wnt activity during this window of development and Id2-deficient intestinal epithelial tissue had more Lgr5+ cells starting at E9.5 compared to controls [111]. Evidence also suggested that Id2 deletion increased Wnt/β-catenin signaling activity in these animals.…”
Section: Early Intestine Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of The EMBO Journal, Nigmatullina et al (2017) show that maturation of Lgr5 + progenitors in the small intestinal epithelium during murine embryonic development is controlled by the transcription factor Id2. In this issue of The EMBO Journal, Nigmatullina et al (2017) show that maturation of Lgr5 + progenitors in the small intestinal epithelium during murine embryonic development is controlled by the transcription factor Id2.…”
mentioning
confidence: 96%